The deubiquitinase USP44 promotes Treg function during inflammation by preventing FOXP3 degradation. (9th July 2020) - Yang, Jing; Wei, Ping; Barbi, Joseph; Huang, Qianru; Yang, Evan; Bai, Yakun; Nie, Jia; Gao, Yanhang; Tao, Jinhui; Lu, Ying; Xie, Chichu; Hou, Xiaoxia; et al.
Abstract: The transcription factor forkhead box P3 (FOXP3) is essential for the development of regulatory T cells (Tregs) and their function in immune homeostasis. Previous studies have shown that in natural Tregs (nTregs), FOXP3 can be regulated by polyubiquitination and deubiquitination. However, the molecular players active in this pathway, especially those modulating FOXP3 by deubiquitination in the distinct induced Treg (iTreg) lineage, remain unclear. Here, we identify the ubiquitin‐specific peptidase 44 (USP44) as a novel deubiquitinase for FOXP3. USP44 interacts with and stabilizes FOXP3 by removing K48‐linked ubiquitin modifications. Notably, TGF‐β induces USP44 expression during iTreg differentiation. USP44 co‐operates with USP7 to stabilize and deubiquitinate FOXP3. Tregs genetically lacking USP44 are less effective than their wild‐type counterparts, both in vitro and in multiple in vivo models of inflammatory disease and cancer. These findings suggest that USP44 plays an important role in the post‐translational regulation of Treg function and is thus a potential therapeutic target for tolerance‐breaking anti‐cancer immunotherapy. Synopsis: The ubiquitin‐specific peptidase 44 (USP44) interacts with FOXP3 and stabilizes the transcription factor by removing K48‐linked ubiquitin modifications. USP44 is essential for the establishment of fully functional regulatory T cells. USP44 is a deubiquitinase for FOXP3 and is up‐regulated via TGF‐beta signaling. USP44 cooperates with USP7 to stabilize FOXP3. Tregs with USP44 deficiency are less effective suppressors than wild type controls. Abstract : The ubiquitin‐specific peptidase 44 (USP44) interacts with FOXP3 and stabilizes the transcription factor by removing K48‐linked ubiquitin modifications. USP44 is essential for the establishment of fully functional regulatory T cells.